A study on the correlation between hyperuricemia and TG/HDL-c ratio in the Naxi ethnic group at high-altitude regions of Yunnan - Han, Dongmei; Yao, Yaqi; Wang, Fengshuang; He, Wenjing; Sun, Tianbao; Li, Han (Frontiers in Medicine, 2024)
The aim of this study is to explore the risk factors for hyperuricemia (HUA) in the Naxi ethnic population residing in high-altitude areas of Yunnan, China, and assess the clinical value of the triglyceride/high-density lipoprotein cholesterol ratio (TG/HDL-c) as a diagnostic marker.In this cross-sectional study, clinical data were collected from the health checkup population in the People's Hospital of Yulong Naxi Autonomous County, Yunnan Province, from January 2021 to January 2023. Participants were divided into quartiles based on TG/HDL-c ratio (Q1, Q2, Q3, Q4) for group analysis using chi-square tests, t-tests, and rank sum tests. Logistic regression analysis and linear regression models were employed to further investigate the correlation between hyperuricemia prevalence and TG/HDL-c ratio in this high-altitude Naxi population.Results: A total of 714 participants with health checkup were included in the study ,the average age was 41.21±11.69 years, of which 61.5% were male and 38.5% were female. The mean uric acid level was 388.51±99.24. After correcting for confounding factors, TG/HDL-c, serum creatinine (Scr), blood urea nitrogen (BUN), TG, HDL-c, red blood cells (RBC), and hemoglobin (Hb) showed a positive correlation with blood uric acid. Further analysis involved categorizing the TG/HDL-c ratio from a continuous variable to a categorical variable using quartiles. The fully adjusted model showed consistent results with the trend observed in the continuous variable analysis when considering the TG/HDL-c ratio as a categorical variable. Additionally, in all unadjusted and adjusted models, the serum uric acid (SUA) levels in the high TG/HDL-c ratio group were significantly higher than those in the low TG/HDL-c ratio group (trend P < 0.001). Further linear relationship analysis indicated that after adjusting for covariates, there was an approximate linear relationship between TG/HDL-c and SUA levels, with a coefficient (β) of 5.421.The prevalence of hyperuricemia is high in high-altitude areas of Yunnan, showing a nearly linear positive correlation with the TG/HDL-c ratio. Monitoring TG/HDL-c levels may benefit patients with hyperuricemia.